Filipino American psychology a handbook of theory, research, and clinical practice - Nadal, Kevin L.; Libtech/IgLibrary. (Hoboken, New Jersey John Wiley & Sons, 2011)
Addressing the mental health needs of the Filipino American population - an often invisible, misunderstood, and forgotten group - Filipino American Psychology provides counselors and other mental health practitioners with the knowledge, awareness, and skills they can use to become effective and culturally competent when working with their Filipino American clients.
Filipino and Filipino American cultural values -- Racial and ethnic identity development for Filipino Americans -- Colonial mentality of Filipino Americans -- Filipino American groups and communities.
Previously published in Bloomington, Indiana by AuthorHouse, ©2009.
Includes bibliographical references (p. 265-287) and index.
Keywords: Filipino Americans -- Ethnic identity; Filipino Americans -- Psychology; Filipino Americans -- Social conditions; Electronic books